The Impact of Covid 19 and Commodification on Tourism Religious Islam: From Spiritual for Experience Tour - Lestari, Mei (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Governments around the world are deeply concerned about how difficult it is for Hajj pilgrims to halt their travel movements during COVID-19 restrictions and national lockdown periods. This pandemic has had a significant impact on pilgrimage tourism in Mecca because since 2020, gatherings at pilgrimage sites have been prohibited. In other words, the Saudi government expanded the hospitality, tourism, and telecommunications sectors in general and modernized Mecca's tourism infrastructure in particular, turning it into a modern city, to take advantage of the increasing demand for religious tourism and to maximize economic benefits (Pecenoni et al., 2012). The desire for increased luxury and comfort suggests that the Hajj has evolved into a more "branded" commercial event. This study also points to the need for further investigation to fully understand the nature of Hajj monetization for religious tourism in general. The spiritual congregation experience is transformed into a counter-experience, a tourist attraction. Additionally, the spiritual congregation experience is transformed into a tourist attraction, a rival experience. violates and endangers the principles of the Hajj pilgrimage and the teachings of the Prophet Muhammad SAW which prioritizes equality, modesty and not showing off. The aim of this report is to begin to discuss the impact of the commodification of the Hajj. The results of pilot research (focus group) on Hajj pilgrims in England over the previous three years are discussed specifically in this report. According to this research, the Hajj has become a commodity, at least for those who undertake it; not only is the experience more “touristy”.